PENINGKATAN KEMAMPUAN KOMUNIKASI MATEMATIS MELALUI MODEL PEMBELAJARAN APTITUDE TREATMENT INTERACTION - Adi Suarman Situmorang (MES: Journal of Mathematics Education and Science, 2023)
The purpose of this study was to determine the increase in students' mathematical communication skills after being taught using the Aptitude Treatment Interaction (ATI) learning model in the Mathematics Education study program, HKBP Nomensen University Medan Academic Year 2022/2023. The population in this study were all students of Mathematics Education, with a sample consisting of 30 people, namely students who attended lectures evaluating learning outcomes in mathematics. The instrument used is a test item of mathematical communication ability. The results of this study were then tested by analysis of variance to answer the proposed research objectives. The data obtained from the research results show that the data is normally distributed because the results of the calculations when testing the requirements using SPSS, the sig. 0.05 is obtained. The results of the data analysis also show that the analysis model designed is valid so that it can prove that the increase in communication skills is influenced by the learning model. From the results of calculating Multiple Comparisons with the Scheffe test, it can be concluded that learning with the ATI model affects ability improvement at all ability levels, whereas the conventional model only affects high levels.